Real Time Digital Controller of Grid Connected Doubly-Fed Induction Wind Turbine Generator - Mesbah, Mohsen; Islam, Syed (United International University, 2012)
In this paper, a real time digital hardware simulation tool to study the performances and responses to grid disturbances of Doubly Fed Induction Generators (DFIGs) is presented. The simulator is a scaled down version of a DFIG wind turbine generator capable of experimenting with various control algorithms and compatibility to grid connection issues under grid disturbances. The paper discusses design, component selection, digital signal processing (DSP) and implementation issues. Experimental results are presented to demonstrate the effectiveness of the simulator.